A parallel arm randomised controlled trial to achieve remission in patients with type 2 diabetes mellitus through dietary and behavioural interventions: a study protocol - A. Singh; J. S. Thakur (Сеченовский вестник, 2025)
Background. Type 2 diabetes mellitus (T2DM) poses a significant challenge to healthcare, with its prevalence escalating to epidemic proportions. The aging population, coupled with the increasing burden of T2DM, is exerting immense pressure on healthcare systems worldwide. Therefore, there is a critical need to design and validate innovative interventions to mitigate the effects of this disease. This randomised control trial aims to achieve remission in Indian patients aged 18 years and older diagnosed with T2DM through dietary and behavioural interventions.Materials and methods. A total of 290 participants with T2DM will be recruited from Indira Colony Urban Enclave, the field practice area of the Department of Community Medicine and School of Public Health at Post Graduate Institute of Medical Education and Research, Chandigarh. Participants will be equally allocated into two arms: intervention (n = 145) and control (n = 145). There will be five measurement timepoints: baseline, 2nd, 4th, 6th and 9th months postrandomisation. The intervention will implement a range of strategies to increase physical activity and promote dietary transitions through behaviour change among patients. The interventions will be designed ensuring a structured approach to behaviour change. Patients from the intervention arm will receive oral hypoglycaemic agents for the first six months of the trial. After this period, medication will be gradually tapered. Patients from the control arm will continue to receive standard care throughout the study. The primary outcome is the number of patients achieving remission of T2DM through behavioural and dietary interventions.Conclusions. The novelty of this trial lies in its focus on community-based settings, unlike other studies that primarily target clinical or hospital-based environments to achieve clinical outcomes. The intervention integrates dietary and behavioural changes into the community’s cultural, socioeconomic, and dietary habits, making it practical and sustainable for patients to adopt and maintain the lifestyle changes needed for remission.